The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1976
DOI: 10.1093/infdis/133.5.548
|View full text |Cite
|
Sign up to set email alerts
|

Hypertriglyceridemia Produced by Endotoxin: Role of Impaired Triglyceride Disposal Mechanisms

Abstract: The role of Salmonella typhimurium endotoxin in producing hypertriglyceridemia was investigated in 70 male rhesus monkeys. Dose-response studies were performed with 0.3-9.0 mg of endotoxin/kg injected intravenously; free fatty acids and triglycerides were measured during the subsequent 8 hr. The effect of endotoxin on lipid disposal mechanisms was assessed by both intravenous lipid-loading tests and total plasma lipolytic activity after administration of heparin. The possible interference of endotoxin with lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
37
0
2

Year Published

1977
1977
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(42 citation statements)
references
References 14 publications
3
37
0
2
Order By: Relevance
“…These mediators are responsible for metabolic and physiological changes that ultimately lead to a pathological situation. Changes in lipid metabolism during sepsis comprise hypertriglyceridemia due to an increased hepatic triglyceride-rich lipoprotein synthesis (11)(12)(13), inhibition of adipose tissue lipoprotein lipase activity (14), and a decreased lipoprotein clearance (11,15,16).…”
Section: Introductionmentioning
confidence: 99%
“…These mediators are responsible for metabolic and physiological changes that ultimately lead to a pathological situation. Changes in lipid metabolism during sepsis comprise hypertriglyceridemia due to an increased hepatic triglyceride-rich lipoprotein synthesis (11)(12)(13), inhibition of adipose tissue lipoprotein lipase activity (14), and a decreased lipoprotein clearance (11,15,16).…”
Section: Introductionmentioning
confidence: 99%
“…Hyperlipidemia, primarily due to the accumulation of VLDL, is one such metabolic aberration (2,3). Hyperlipidemia in models of infection has been observed in a wide variety of species including humans, monkeys, rabbits, dogs, and rats (2)(3)(4)(5)(6)(7)(8)(9)(10). Studies have shown that model infections result in both a decrease in the metabolism ofcirculating lipoproteins (8,9) and an increase in hepatic lipid synthesis (10).…”
Section: Introductionmentioning
confidence: 99%
“…Key words: lipoproteins * triglycerides * lipopolysaccharide * cytokines * liver mediate the acute phase response, a change in the hepatic synthetic program with increased production of acute phase proteins that aid host defense (4)(5)(6)(7). The host response to infection also includes cytokine-mediated changes in intermediary metabolism such as hypertriglyceridemia (8,9), which is due to both increases in hepatic triglyceride-rich lipoprotein synthesis (10,11 ) and decreases in lipoprotein lipase-mediated lipoprotein clearance ( 12,13).…”
mentioning
confidence: 99%